A comparative evaluation of properties of denture base materials processed with different processing methods: a preliminary study. - Bhavana Lahari, Sangam; Pottem, Srinivas Rao; Ram Koti Reddy, Anyam; Tannamala, Pavan Kumar; Saran Babu, Kalamalla A; Manogna , Vangala R L (International Journal of Dental Materials, 2021)
Background: The use of the traditional polymerization process of dentures necessitates a lot of time and energy. To depreciate these factors, a different processing method could be studied. Aim: This study was aimed to evaluate and compare the properties of denture base resin material processed with conventional curing and pressure-pot method. Materials and methods: A total of 30 specimens with distinct dimensions were fabricated with the denture base materials. The specimens were divided into two groups with 15 each, and they were processed using conventional heat-curing and pressure-pot processing, respectively. Each group is subdivided into three groups with five specimens in each for evaluating flexural strength, water sorption, and residual monomer, respectively. Flexural strength was measured using a 3-point bending test with a Universal testing machine. Water sorption was assessed by measuring the weight of the specimens after immersing them in distilled water. Residual monomer content was evaluated using a UV spectrophotometer. The obtained data were statistically analysed using an independent t-test. Results: A slight increase in flexural strength was observed in the pressure processed specimens. However, no significant differences (p=0.131) were observed in the flexural strength between the groups. Less water sorption percentage was observed with the pressure processed acrylic resin specimens, and a significant difference (p=0.047) was observed between the groups. A slightly more amount of residual monomer content was seen in the acrylic specimens processed conventionally. Conclusion: Pressure-pot curing may be used for processing denture base acrylics as it provides properties similar to that of the conventional curing method.